Actinomycotic Mycetoma Of Scalp Caused By Actinomadura Pelletierii-A Report Of Two Cases - Selvam A; Sentamilselvi G; Kamalam A; Janaki C; Janaki V R (Wolters Kluwer Medknow Publications, 1999)
Two cases of actinomycotic mycetoma of the scalp caused by Actinomadura pelletierii are described with their classical clinical, mycological, histopathological and radiological features. The first case was treated with contrimoxazole as monotherapy. She developed recurrence later, even while on therapy. The second case was treated with combined oral cotrimoxazole and parenteral streptomycin with a good response.